Effectiveness of Using E-Senbud as Android-Based Art Culture Learning Media at SMAN 1 Sumbawa Besar - Zactian, Ageng; Umar, Umar; Maulidyawati, Desi (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2022)
Learning is a process and effort to create learning conditions that optimally develop students’ skills, interests, and talents so that they can achieve their competencies and goals. The achievement of learning objectives depends on the use of media strategies and the use of media. The purpose of this study was to determine the feasibility and effectiveness of using E-Senbud as a learning medium to increase student learning productivity at SMAN 1 Sumbawa Besar. Collecting data using questionnaires and field observations on a sample of 100 students. The type of research used by the researcher is qualitative research with descriptive research characteristics. The results of the feasibility and effectiveness aspects of the test by material experts obtained an average score of 94,13%, the linguists obtained a percentage score of 90,00%, and the results of the assessment according to student responses obtained an average score of 96.00% with very feasible criteria. So it can be concluded that the use of E-Senbud learning media in cultural arts subjects is very effective in increasing the learning productivity of SMAN 1 Sumbawa Besar students.